Pembuatan Ensiklopedi Prosesi dalam Upacara Adat Perkawinan di Tarusan Pesisir Selatan - Putri, Nindy Aprilia; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper aims to describe the technique of making encyclopedias procession in traditional ceremony of marriage in Tarusan Pesisir Selatan. The method used is descriptive research method with data collection technique through interview. Data collection through interviews was conducted with traditional leaders in Pesisir Selatan. Based on the discussion, it can be concluded that the stages in making encyclopedias procession in traditional ceremony of marriage in South Coastal Tarusan as follows: (1) data collection, (2) making cover, (3) making of introduction, (4) making table of contents,(5)making index.Keyword: ceremony, encyclopedia, marriage, procession.